2017
DOI: 10.1097/mib.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Crohnʼs Disease

Abstract: Background Patients with Crohn's disease (CD) encompass a heterogeneous disease spectrum, with variable healthcare utilization and expenditure patterns. Lémann Index (LI) is a metric that quantifies cumulative bowel damage and has shown utility in delineating distinct disease phenotypes. Aim To characterize the financial burden from all medical care in a CD cohort in relation to variations in LI-based disease phenotypes. Methods CD patients with 5 year(y) follow-up from a prospective registry were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Previous studies estimate the annual cost of CD to be between $18,637 and $24,000 8,43. A recent study by Rao et al in published 2017 determined the interquartile range of cost at even between $9128 to $48,079 4. That our results, determined independently of any claims database data, are in line with cost data from claims databases lends further support to our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies estimate the annual cost of CD to be between $18,637 and $24,000 8,43. A recent study by Rao et al in published 2017 determined the interquartile range of cost at even between $9128 to $48,079 4. That our results, determined independently of any claims database data, are in line with cost data from claims databases lends further support to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…The economic burden of CD is also high 3. Median (interquartile) cost of care over 5 years has been reported at $116,838 ($45,643 to $240,398) 4Figure 1Comparison of major surgical outcomes between the model and published literature on Crohn’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…In today’s era of effective but costly pharmacotherapies, one driver of the cost of care for patients with IBD appeared to be in outpatient pharmacy utilization. Based on preliminary data here and in other research, 10 , 18 , 19 supported by the overall cost trends in prescription drugs in the United States, 20 , 21 the Foundation identified the cost of biologics as a key strategic area for improved cost-effectiveness, patient advocacy, and patient-centeredness. Facilitating better access to appropriate medications and minimizing transference of drug costs from payers to patients are 2 integral components of improved patient-centered care as identified by the IBD Cost of Care Task Force.…”
Section: Discussionmentioning
confidence: 80%
“…We found that direct costs varied widely between studies. A number of studies reported direct costs, but did not include direct out-of-pocket costs to patients, rather reporting on the direct costs of health care (26,30,31,36). Overall, patients with UC incurred lower direct costs than patients with CD.…”
Section: Discussionmentioning
confidence: 99%